Effects of iron ions, doping methods and nanotubular morphology on TiO2 solar photocatalytic performance - Rafik Melki (IWA Publishing, 2021)
The effects of Fe2+ and Fe3+ as TiO2 cocatalysts were studied, and the experimental results showed that Fe3+ was more efficient than Fe2+, which needed an intermediate reaction to produce hydroxyl radicals. TiO2 was modified with the aim of improving its structural, optical, and adsorption properties, thus improving its photocatalytic performance. The light range of the catalyst activation process was expanded, which increased the catalyst's ability to absorb visible light. Consequently, this study exploits solar energy in photocatalysis by Fe ion doping using different methods, including impregnation, photodeposition, solvothermal doping, and hydrothermal doping, and evaluates the influence of each doping method on TiO2 optical properties and photocatalytic activity. Enhancing the catalyst adsorption capacity by morphologically modifying TiO2 nanoparticles into nanotubes using the hydrothermal method increases the catalyst surface area from 55 to 294 m2/g, as shown in the SEM and BET results. The effect of combining morphological changes and Fe3+ doping on TiO2 activity was evaluated. We observed a reduction in the TiO2 band gap from 3.29 to 3.01 eV, absorption edge widening, and an increase in the specific surface area up to 279 m2/g; thus, the synthesized catalyst eliminated Cefixime in 120 min. HIGHLIGHTS The iron ion photocatalytic degradation mechanism is studied.; TiO2 nanotubes with high photocatalytic activity are explained.; Hydrothermal doping improves TiO2 structural, optical and physical properties.; A comparative study of four different Fe3+/TiO2 doping methods is performed.; Fe3+ use as a cocatalyst may, in some cases, be more efficient than its use as a dopant.;